The Noctuoidea of the Swietokrzyski National Park (Poland) (Lepidoptera: Erebidae, Nolidae, Noctuidae) - J. Nowacki; R. Wasala (SHILAP, 2021)
This paper presents the results of a long-term study (2008-2020) of the Noctuoidea (Erebidae, Nolidae, Noctuidae) inhabiting the various ecosystems in the Swietokrzyski National Park (S´NP) (South Poland). A total of 273 Noctuoidea species were recorded, i.e. 54% of all the Noctuoidea ever recorded in Poland; 127 of them were recorded for the first time in the study area. These results show unequivocally that the S´NP plays a major role in the preservation of Noctuoidea biodiversity in both Poland and Europe as a whole. A good number of stenotopic species occur here, which are rare and often endangered in both Poland and central Europe, for example: S. costaestrigalis (Stephens, 1834), S. taenialis (Hübner, [1809]), C. electa (Vieweg, 1790), N. cristatula (Hübner, 1793), N. degenerana (Hübner, [1799]), L. c-aureum (Knoch, 1781), A. asclepiadis ([Denis & Schiffermüller], 1775), S. scrophulariae ([Denis & Schiffermüller], 1775), A. perflua (Fabricius, 1787), H. respersa ([Denis & Schiffermüller], 1775), A. furvula (Hübner, [1808]), P. scita (Hübner, 1790), I. contusa (Freyer, 1849), A. pulmonaris (Esper, 1790), D. convergens ([Denis & Schiffermüller], 1775), A. syriaca Osthelder, 1933, E. ochroleuca ([Denis & Schiffermüller], 1775), X. graminea (Graeser, 1889), H. ultima Holst, 1965, H. cavernosa (Eversmann, 1842), P. biren (Goeze, 1781), O. opima (Hübner, [1809]), N. interjecta Hübner, [1803], and A. bigramma (Esper, 1790).